Indonesia Government Public Communication in the Covid-19 Pandemic Handling - Sahlan, Muhammad (Fakultas Dakwah IAIN Purwokerto, 2021)
Since Covid-19 broke out in Indonesia, the public has monitored various government policies in dealing with these health disasters. However, policies run slowly; it gives rise to diverse public opinion. These multiple opinions become a form of communication between the government and society. However, the government does not fully capture people’s views, so people feel they do not receive government policies’ feedback. The purpose of this research is to find out how the Indonesian government’s public communication is in dealing with the Covid-19 pandemic. The research used a descriptive qualitative method using data during Covid-19. This study explains how the debate of government and community communication occurs in the form of public opinion. Various forms of public opinion from adverse to positive states become message instruments aimed at the government. This instrument then forms communication in the form of action as a sense of moral panic due to the absence of a back answer to the opinion expressed. So, these opinions are only as answers and realized by society in phenomena.